THE PECULIARITIES OF THE SPEECH COMPREHENSION PROCESS IN CHILDREN WITH DYSARTHRIA (American Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the specifics of the development of speech understanding in dysarthric children, the course of speech in pseudobulbar dysarthria, the movements of the muscles of the articulatory speech apparatus and their characteristics.